2005
DOI: 10.1111/j.1471-0528.2004.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury ten years after: subjective and objective long term effects

Abstract: Objective To establish the long term effects of obstetric anal sphincter rupture.Design Prospective observational study.Setting University hospital in Sweden.Population Eighty-two women from a prospective study from 1990 to compare anorectal function after third degree tear. Methods Women completed a structured questionnaire, underwent a clinical examination and anorectal manometry, endoanal ultrasound (EAUSG) with perineal body measurement. Main outcome measures Symptoms of anal incontinence, sexual symptoms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
2
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(94 citation statements)
references
References 26 publications
3
85
2
4
Order By: Relevance
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 55%
“…The limitation of the present study was the overall response rate of 36%, which may appear low in comparison to other studies [5,7,[9][10][11]. However, we did not contact women by phone before sending the questionnaires [10,11] nor ask them to participate in the study in the direct postpartum period [6], or considered a group of women that had already participated in a previous study [5,7,9], which might all induce a selection bias. Similar response rates (32-33%) were obtained by others who mailed a brief questionnaire about pelvic floor symptoms in an unselected group of women after vaginal birth [13].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Second is the trauma related to instrumentation, and third is surgical episiotomy. Women who sustain thirddegree obstetrical tear develop FI soon after delivery if muscles are not properly repaired (13). However, in the significant majority of women, injury to the anal sphincter and other pelvic floor muscle is occult.…”
mentioning
confidence: 99%